Beragama di Pulau Pariwisata Internasional : Pengalaman Toleransi Komunitas Muslim di Lombok Nusa Tenggara Barat - Akhmad Asyari; Kadri Kadri; Jumarim Jumarim (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
Muslim residents in tourist destinations are often seen as victims of the socio-religious impact of the tourism industry in their area. In contrast to this view, this article sees Muslims as important actors in maintaining Islamic traditions amid the negative influence of the tourism industry. This qualitative study focuses on revealing the religious experiences of Muslims in three international tourism islands on Lombok Island, particularly in maintaining Islamic teachings and synchronizing them with tourism activities. The results showed that Muslim residents in Gili Trawangan, Gili Gede and Kuta Village implemented the teachings of tolerant Islam to accommodate religious and economic interests in tourism destinations. Islamic teachings are maintained through independent, institutional-based strengthening, and strengthening by the government. This study recommends the importance of maintaining a tolerant Islamic tradition in international tourism destinations to support tourism and maintain Islamic teachings.